Analysis of the liquidity risk in credit unions: a logit multinomial approach - Rosiane Maria Lima Gonçalves; Marcelo José Braga (RAC: Revista de Administração Contemporânea, 2008)
Liquidity risk in financial institutions is associated to balance between working capital and financial demands. Other factors that affect credit union liquidity are an unanticipated increase of withdrawals without an offsetting amount of new deposits, and the lack of ability in promoting the product geographical diversification. The objective of this study is to analyze Minas Gerais state credit union liquidity risk and its factor determinants. Financial ratios and the multinomial logit model are used. The cooperatives were classified in five categories of liquidity risk: very low, low, medium, high and very high. The empirical results indicate that high levels of liquidity are related to smaller values of the outsourcing capital use, immobilization of the turnover capital, and provision ratios. So, they are associated to larger values of the deposit total/credit operations, and asset growth ratios.